Efektivitas Video Tutorial Dalam Meningkatkan Keterampilan Vokasional Membuat Macrame Wall Bagi Anak Tunarungu Kelas IX di SLB Luak Nan Bungsu - Usman, Andri (journal of residu, 2019)
This research was conducted because of problems found in special schools at the level of the Special Senior High School in SLB Luak Nan Bungsu. In this school the subject of handicraft skills is less attractive to students. To increase students' interest in handicraft skills, researchers provide an example of a new craft skill that is making macrame wall. This study aims to improve the skills to make macrame walls for deaf children named Kevin. At the moment Kevin sits in class IX in SLB Luak Nan Bungsu. The research method is an experimental method with a Single Subject Research approach. The design used is A-B-A. Measurement and data collection in the first baseline (A1) condition is carried out continuously for 5 meetings. Next on the giving of intervention (B) by using a video tutorial given during 6 meetings. Observation of the child's condition further on the second baseline (A2) conducted during 5 meetings. Data collection techniques are direct observation and test. The results of this study indicate the condition of Kevin's handicraft skills in making macrame wall obtain positive results. Based on the results of data analysis, it shows that video tutorials are effective in improving craftsmanship skills in making macrame wall in deaf children.